Peculiarities of Scientific Texts and Translation of Terms (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article covers the essential aspects of scientific texts and the translation of terms. It discusses common challenges and provides examples from different scientific fields. This abstract investigates the distinctive linguistic features of scientific texts, including their dense terminology, formal style, and precise use of language. It explores the inherent challenges in translating these texts, focusing on the difficulties posed by the translation of technical terms, including neologisms, ambiguous terms, and culturally specific concepts. The abstract further examines various translation strategies employed to overcome these challenges, considering the balance between accuracy, clarity, and cultural appropriateness within the target audience.